Mirage : Napoleon's scientists and the unveiling of Egypt - Burleigh, Nina (Harper, 2007)
Two centuries ago, only the most reckless Europeans dared traverse the Middle East. Its history and peoples were the subject of myth and speculation--and no region aroused greater interest than Egypt. It was not until 1798, when an unlikely band of scientific explorers traveled from Paris to the Nile Valley, that Westerners received their first real glimpse of what lay beyond the Mediterranean. Under the command of Napoleon Bonaparte, a small corps of Paris's brightest left the safety of their laboratories, studios, and classrooms to embark into the unknown--some never to see French shores again. Over 150 astronomers, mathematicians, naturalists, physicists, doctors, chemists, engineers, botanists, artists--even a poet and a musicologist--accompanied Napoleon's troops into Egypt. They approached the land not as colonizers, but as experts in their fields of scholarship, meticulously categorizing and collecting their finds, and secured their place in history as the world's earliest-known archaeologists.--From publisher description.